Zoneamento de impactos ambientais cotejados aos instrumentos jurídicos na bacia hidrográfica do Arroio Cadena, município de Santa Maria - RS - Garcia, Valéria Quevedo (2012)
Failure to comply with environmental legislation by municipal governments is the main objective of this work, which aims to analyze the environmental vulnerability caused by different modes of life of people living in areas with aggravating physical environment, thereby undermining the entire system survival and, especially, the permanent preservation areas – APP, in Santa Maria, RS. In addition to a deep analysis on legislative resources, we also used the geoprocessing for this type of analysis, which is widespread and recognized worldwide by allowing representing different variables in the same territory and, therefore, facilitating discussions, proving them scientifically. This study developed an approach based on data considered essential to the quality of life and environment in urban areas, education and income on three different levels. The intention was to develop a methodology to assist the public in the administration and reflexion of existing environmental legislation and also the communities where the problems are located with greater negative impacts, so that appropriate policies are prioritized in decision making. It can therefore be concluded that much of the population living in APP has reduced quality of life and is environmentally vulnerable.